Methodological strategies for the development of multiple intelligences in tenth year students - Zambrano, Ángela Veronica Hidrovo; Cantos, Ubety del Carmen Cedeño; Chilan, Yandri Guillermo Toala (International research journal of management, IT and social sciences, 2021)
The application of effective methodological strategies based on the theory of multiple intelligences is the fundamental objective of research to determine and verify the potential of students at different levels of learning, according to academic tasks and activities, both theoretically and practically. The type of research is argumentative, with scientific strategies developed by various authors. It was necessary to apply analytical, synthetic, comparative methods and a bibliographic review in information sources, through documents, scientific articles, journals, among other research instruments, to identify different teaching-learning models of a pedagogical and educational nature. high impact, in addition to methodological strategies that allowed to argue the theoretical basis of the authors, the systematic they proposed, for which each of their arguments and explanations were analyzed. The different types of skills were compared through the comparative method to contrast each of the methodologies and strategies exposed by the researchers, highlighting what is based on each of them and how they differ from one to the other, as well as the advantages and disadvantages possessed by each of the models taken, generating a cluster of ideas that continued to choose the best methodological strategy to apply in the classroom.